In-situ irradiation tolerance investigation of high strength ultrafine tungsten-titanium carbide alloy. (1st February 2019) - El-Atwani, O.; Cunningham, W.S.; Esquivel, E.; Li, M.; Trelewicz, J.R.; Uberuaga, B.P.; Maloy, S.A.
Abstract: Refining grain size and adding alloying elements are two complementary approaches for enhancing the radiation tolerance of existing nuclear materials. Here, we present detailed in-situ irradiation research on defect evolution behavior and irradiation tolerance of ultrafine W-TiC alloys (thin foils) irradiated with 1 MeV Kr +2  at RT and 1073 K, and compare their overall performance to pure coarse grained tungsten. Loop Burgers vector was studied confirming the presence of <100> loops whose population increased at high temperature. Loop density, average loop area, and overall damage are reported as a function of irradiation dose revealing distinct defect evolution behavior from pure materials. The overall damage generally followed the average loop size trend, which decreased with time for both temperatures, but was higher at 1073 K and attributed to biased vacancy sink behavior of the TiC dispersoids evidenced by large vacancy clusters on their interfaces. By comparison, the overall loop and void damage in pure tungsten was larger by a factor of six and two, respectively. The improved irradiation damage resistance in the alloys is thus attributed to the effect of dispersoids in 1) the enhancement in annihilating defects and mutual defect recombination due to both dispersoids and a higher grain boundary density; 2) decreasing the loop mobility, causing shrinkage and annihilation of loop density, which was confirmed via in-situ video. Several mechanisms are illustrated to describe the performance of the complex alloy system. The results motivate further experimental and modeling research that aims to understand the many different phenomena occurring at different time scales. Graphical abstract: Damage evolution behavior for pure W and ultrafine W-TiC alloy irradiated with 1 MeV Kr +2  at 1073 K. Image 1